Impact of the economic crisis on employees: Results of an online-survey by the 'LohnSpiegel' project - Reinhard Bispinck; Heiner Dribbusch; Fikret Öz (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2010)
Many firms have responded to the economic crisis by reducing em-ployee numbers, introducing short-time working, and cutting pay and benefits. However, the experiences of individual employees vary con-siderably, depending on economic sector and type of employee. These are the findings of a recent online survey conducted by the LohnSpiegel project, a pay database managed by the Collective Bargaining Archive of the WSI institute at the Hans Böckler Foundation in Düsseldorf, Germany. – – Auf die Wirtschaftskrise reagieren viele Betriebe mit Personalabbau, Kurzarbeit und Abstrichen bei Lohn und Gehalt. Zwischen den Branchen und Beschäftigtengruppen bestehen aber deutliche Unterschiede. Zu diesem Ergebnis kommt eine Online-Erhebung des Projekts LohnSpiegel, die vom WSI-Tarifarchiv der Hans-Böckler-Stiftung durchgeführt wurde. Dieser WSI-Report stellt die Gesamtergebnisse vor und präsentiert darüber hinaus detaillierte Daten für die Metallindustrie, die chemische Industrie und den Finanzdienstleistungssektor.
urn:nbn:de:101:1-201602166325
Keywords: 330